Rare Case of Pelvic Peritonitis Misdiagnosed by Ovarian Malignancy, Referred Following Chemotherapy - Arab, Maliheh; Ashoori Barmchi, Adele; Neda Kazemi, Seyedeh; Gharib, Atoosa (Reports of Radiotherapy and Oncology, 2015)
Background: Tuberculosis is an old disease that is still one of the main causes of death in the world. Nearly 60-67% of TB patients are from developing countries. Proper treatment results resolution in almost all cases. Pelvic TB occurs in about 10% of pulmonary TB patients. The present case reviews a TB case misdiagnosed in a young woman with a pelvic mass and ascetic fluid. Case Report: A 35-year-old woman living in an area exposed to immigrants from TB endemic regions presented with ascetic fluid and a pelvic mass and high titer of sacrum CANS (350). She was misdiagnosed with ovarian malignancy due to a positive malignancy report of ascetic fluid. After chemotherapy she was referred for definite operation. In the surgical field, a TB diagnosis was made. Conclusions: Review of preoperative reports and careful history of the case revealed that had an awareness about TB existed in this case, a proper diagnosis might have been made before the erroneous chemotherapy. She was young, suffering from pelvic pain, fever, and weight loss coming from an exposed area to TB cytology of ascetic fluid included dominancy of lymphocytes. Relying on a positive cytology finding for malignancy might be questionable.